A Framework for Ethical Integration of Artificial Intelligence Tools in Medical Research and Writing - Fareeha Farooq , Farooq Azam Rathore (Journal of Islamic International Medical College)
Abstract The global landscape of medical research and writing over the last decade has been evolving rapidly. It got a major boost by the public launch of ChatGPT in November 2022. It has been further accelerated due to the widespread availability and easy access to a variety of artificial intelligence (AI) tools based on Large Language Models (LLMs).1 The use of AI tools in medical research and writing is on the rise. However, many students, faculty members and researchers particularly in developing countries are still unclear on the transparent and ethical integration of the AI tools in research and writing. We propose a framework for the appropriate integration of AI in medical research and writing in context of a developing country like Pakistan. It highlights responsible and transparent use of AI tools, discuss authorship in the era of AI tools and how to ensure scientific integrity.